Indolent In Situ B-Cell Neoplasms With MYC Rearrangements Show Somatic Mutations in MYC and TNFRSF14 by Next-generation Sequencing. (December 2019) - Kumar, Jyoti; Butzmann, Alexandra; Wu, Sharon; Easly, Samantha; Zehnder, James L.; Warnke, Roger A.; Bangs, Charles D.; Jangam, Diwash; Cherry, Athena; Lau, James; Nybakken, Grant; Ohgami, Robert S.
Abstract : Systemic high-grade B-cell lymphomas (HGBCLs) with MYC gene rearrangements are clinically aggressive. In situ lesions with indolent behavior have not been described to date. We have identified 2 cases of in situ B-cell neoplasms with MYC rearrangements (IS-BCN, MYC + ) occurring, and focally confined to ⩽4 lymphoid follicles in otherwise healthy individuals and without clinical progression despite minimal intervention (surgical only). Morphologically similar to systemic HGBCLs, the low power view of these lesions showed a starry sky pattern with numerous mitotic figures. High power imaging demonstrated these cells to be medium-large in size with irregular nuclear contours, immature chromatin, and prominent nucleoli. Immunophenotypically these cells were light chain restricted, positive for CD20, CD10, c-Myc, and dim or negative for BCL2 with a Ki67 proliferative index of >95%. By fluorescence in situ hybridization studies, we detected MYC translocations in these cells but no rearrangements in BCL2 or BCL6 . Microdissection of neoplastic cells in these patients followed by targeted next-generation sequencing identified a mutation in MYC, D2N, and an indel in TNFRSF14 . Mutations in ID3 or TCF3 were not identified. Although rare, these lesions should be separated from HGBCLs involving follicles but with systemic spread which has been previously described. Unlike systemic lymphomas with MYC gene rearrangements, these in situ B-cell neoplasms with MYC rearrangements did not require systemic therapy and no progression has been seen in either patient beyond 1 year (29 and 16 mo). Our work offers pathologic and biologic insight into the early process of B-cell neoplasia. Abstract : Supplemental Digital Content is available in the text.